2009 IEEE Symposium on 3D User Interfaces 2009
DOI: 10.1109/3dui.2009.4811212
|View full text |Cite
|
Sign up to set email alerts
|

Tech-note: Multimodal feedback in 3D target acquisition

Abstract: We investigated dynamic target acquisition within a 3D scene, rendered on a 2D display. Our focus was on the relative effects of specific perceptual cues provided as feedback. Participants were asked to use a specially designed input device to control the position of a volumetric cursor, and acquire targets as they appeared one by one on the screen. To compensate for the limited depth cues afforded by 2D rendering, additional feedback was offered through audio, visual and haptic modalities. Cues were delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Target acquisition is one of the most elementary interactions in 3D environments [29]. However, the interaction choice, a critical factor in usability and performance of VR systems, is highly influenced by the task to be performed after target acquisition stage [52].…”
Section: Docking Tasksmentioning
confidence: 99%
“…Target acquisition is one of the most elementary interactions in 3D environments [29]. However, the interaction choice, a critical factor in usability and performance of VR systems, is highly influenced by the task to be performed after target acquisition stage [52].…”
Section: Docking Tasksmentioning
confidence: 99%
“…El-Shimy et al propose using aural and tactile modalities in addition to visual feedback for picking targets in a 3D scene rendered on a regular display (El-Shimy et al 2009). The added modalities are used to provide depth information.…”
Section: Orienting Cues and Information Communicationmentioning
confidence: 99%
“…They also found that auditory and tactile channels alone work better than using visual feedback in this eminently visual task of target acquisition. El-Shimy et al (2009) propose using auditory and tactile modalities in addition to visual feedback for picking targets in a 3D scene rendered on a regular display. The added modalities are used to provide depth information.…”
Section: Comparing Visual Auditory and Tactile Feedbackmentioning
confidence: 99%